Influenza vaccines: the potential benefits of cell-culture isolation and manufacturing - Sankarasubramanian Rajaram; Constantina Boikos; Daniele K. Gelone; Ashesh Gandhi (SAGE Publishing, 2020)
Influenza continues to cause severe illness in millions and deaths in hundreds of thousands annually. Vaccines are used to prevent influenza outbreaks, however, the influenza virus mutates and annual vaccination is required for optimal protection. Vaccine effectiveness is also affected by other potential factors such as the human immune system, a mismatch with the chosen candidate virus, and egg adaptation associated with egg-based vaccine production. This article reviews the influenza vaccine development process and describes the implications of the changes to the cell-culture process and vaccine strain recommendations by the World Health Organization since the 2017 season. The traditional manufacturing process for influenza vaccines relies on fertilized chicken eggs that are used for vaccine production. Vaccines must be produced in large volumes and the complete process requires approximately 6 months for the egg-based process. In addition, egg adaptation of seed viruses occurs when viruses adapt to avian receptors found within eggs to allow for growth in eggs. These changes to key viral antigens may result in antigenic mismatch and thereby reduce vaccine effectiveness. By contrast, cell-derived seed viruses do not require fertilized eggs and eliminate the potential for egg-adapted changes. As a result, cell-culture technology improves the match between the vaccine virus strain and the vaccine selected strain, and has been associated with increased vaccine effectiveness during a predominantly H3N2 season. During the 2017-2018 influenza season, a small number of studies conducted in the United States compared the effectiveness of egg-based and cell-culture vaccines and are described here. These observational and retrospective studies demonstrate that inactivated cell-culture vaccines were more effective than egg-based vaccines. Adoption of cell-culture technology for influenza vaccine manufacturing has been reported to improve manufacturing efficiency and the additional benefit of improving vaccine effectiveness is a key factor for future policy making considerations.